Preparation method of high-performance Micro-LED surface dielectric film

Through pulse magnetron sputtering technology and response surface method optimization process parameters, a high-hard multi-layer anti-reflection film was prepared, which solved the problem of insufficient reflected light and hardness of Micro-LED display screen, improved brightness and contrast, and improved the screen Durability.

CN119194384APending Publication Date: 2024-12-27SHI-CHENG LABORATORY FOR INFORMATION DISPLAY & VISUALIZATION +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411340430.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Micro-LED displays face the problems of reflected light, color cast after splicing and insufficient hardness, which affect the display effect and user experience.

Method used

The multi-layer anti-reflection film is prepared by pulse magnetron sputtering technology, optimize the process parameters through the response surface method, improve the hardness of the film layer, and reduce the reflectance by using the metal/die multi-layer film structure, and realize the film layer by combining spin coating and glueing processes. Preparation.

Benefits of technology

It improves the brightness and contrast of Micro-LED, while also improving the hardness of the glass cover surface, reducing the impact of reflected light, and improving the display effect and screen durability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119194384A_ABST
    Figure CN119194384A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a high-performance Micro-LED (Light Emitting Diode) surface dielectric film, aiming at the problems that the surface reflectivity of an untreated Micro-LED glass cover plate is high and the contrast ratio is influenced, the structure of a Micro-LED surface film layer is optimized by utilizing optical film simulation analysis, and a multi-layer film with the same structure is prepared under different process parameters. A visible spectrophotometer, an atomic force microscope and a microhardness tester are used for characterizing the film layer prepared through experiments. According to the method, the preparation process of the multi-layer antireflection film is further optimized, optimal process parameters are obtained and verified, and the multi-layer antireflection film with high hardness is prepared, so that the effect of protecting the surface of the Micro-LED is achieved while the luminance and the contrast ratio of the Micro-LED are improved, and the service life of the multi-layer antireflection film is prolonged. According to the method, great help is provided for Micro-LED display and projection application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of devices of information display technology, and mainly focuses on the materials and processes of Micro-LED. Background Art

[0002] As the materials and processes of Micro-LED continue to break through, coating technology is also developing. At present, coated products such as glasses, mobile phones, automobiles, hardware and other products have long been inseparable from human life. In recent years, people have paid more and more attention to environmental protection. Electroplating, chemical plating and other coating methods that cause environmental pollution have gradually been replaced by green and energy-saving physical vapor deposition technology. Physical vapor deposition (PVD) technology can prepare thin films composed of various materials such as metal materials and ceramic materials. It has special properties such as optics, electricity, mechanics, and thermal properties. The film performance is stable, the process repeatability is good, the production cycle is short and the output is large. It has become an important method for preparing thin films in today's industrial field.

[0003] Since Micro-LED has the characteristic of self-luminescence, there is no need to install the polarizer required for liquid crystal display (LCD). However, there is reflected light on the screen surface, so the glass cover of the screen generally needs to be treated to eliminate some reflected light to improve the transmittance and contrast of the display. In order to eliminate the influence of ambient light on the display effect, Micro-LED needs to increase the black area on the screen surface, which is generally achieved by coating black solder mask ink on the substrate. Due to the limitation of chip mass transfer technology, the current size of a single Micro-LED is relatively small. According to research, the size of the largest commercial Micro-LED splicing unit in China is only 150cm 2 , large-sized Micro-LED display screens can only be realized by splicing, and circuit boards from different production batches may have ink color differences, resulting in a certain color cast on the screen after splicing, seriously affecting the user experience. At the same time, it is difficult to avoid bumps, scratches and other accidents that may damage the screen in daily use, so Micro-LED products usually have certain requirements for the hardness of the screen. These three problems can be alleviated by preparing a visible light absorption anti-reflection film on the surface of the screen glass cover. Summary of the invention

[0004] Purpose of the invention:

[0005] Because Micro-LED still needs to improve its advantages in optical performance such as brightness and contrast in the display field, the preparation of its surface dielectric film also needs to continue to make breakthroughs. Vacuum evaporation technology and magnetron sputtering technology each have their own advantages and disadvantages in the preparation of anti-reflection films and other optical films. Currently, both PVD technologies have relatively mature applications in the preparation of anti-reflection films. The present invention mainly hopes to obtain a multilayer anti-reflection film with higher hardness, so a pulsed magnetron sputtering device can be used to prepare the sample. The process rules of pulsed magnetron sputtering technology for depositing multilayer anti-reflection films are further analyzed; the hardness of the multilayer anti-reflection film is used as the optimization target, and the response surface method is used to optimize the process parameters for preparing the multilayer anti-reflection film to obtain the optimal process conditions.

[0006] Technical solution:

[0007] The present invention adopts the following technical solutions to solve the above technical problems:

[0008] A method for preparing a high-performance Micro-LED surface dielectric film comprises the following steps:

[0009] Multilayer anti-reflection film samples with the same structure were prepared under different process parameters;

[0010] Measuring the hardness of each prepared multilayer anti-reflection film sample;

[0011] Taking the hardness of the multilayer anti-reflection film as the optimization target, the response surface methodology was used to optimize the process parameters for preparing the multilayer anti-reflection film and the optimal process conditions were obtained.

[0012] Prepare Micro-LED surface dielectric film under optimal process conditions.

[0013] Preferably, the multilayer anti-reflection film comprises, from bottom to top, a substrate, a first metal layer, a first dielectric layer, a second metal layer, and a second dielectric layer.

[0014] Preferably, the material of the first metal layer and the second metal layer is Cr.

[0015] Preferably, the material of the substrate is SiO2.

[0016] Preferably, a pulsed magnetron sputtering device is used to prepare a multilayer anti-reflection film sample, and the specific steps include: processing the incident light into monochromatic light of different wavelengths, utilizing the selective absorption of light of different wavelengths by different substances, and converting the transmitted light into an electrical signal according to the photoelectric effect to achieve the measurement of transmittance and reflectance; fitting the film thickness by the transmittance and reflectance of the film, and then calculating the deposition rate of the film according to the film preparation time, and then completing the preparation of the film through five steps of base pretreatment, film loading, cleaning, film preparation and film removal.

[0017] Preferably, the preparation method of the multilayer anti-reflection film includes: laminating the layers by spin coating, evenly distributing the glue on the surface of each layer, then peeling off the film to isolate the area used for optical transmission, the third step is gluing, and finally curing.

[0018] Preferably, an ellipsometer is used to make polarized light incident at a certain angle onto the multilayer anti-reflection film sample to be tested, and elliptically polarized light is formed after reflection occurs on the surface of the multilayer anti-reflection film sample; the polarizer inside the ellipsometer calculates the optical constants of the dielectric material based on the change in the polarization state of the incident light of the sample to be tested, and the ellipsometer is used in the experiment to measure the optical constants of the film material.

[0019] Beneficial effects: The present invention has the following advantages by using the above inventive method:

[0020] The present invention proposes a method for preparing a high-performance Micro-LED surface dielectric film, which determines the film material of the multilayer anti-reflection film, wherein Cr is selected as the high refractive index material and SiO2 is selected as the low refractive index material; in order to reduce the error between the theoretical value and the actual value of the optical performance of the designed film system, the refractive index and extinction coefficient of the two materials are measured and determined; the deposition rate and surface morphology of the multilayer film prepared under different process parameters are determined, and the effects of different process parameters on the deposition rate and surface morphology of the multilayer film are different. Thus, a structure film system with the best optical performance in brightness and contrast in the five-layer structure is proposed, and the appropriate hardness is achieved. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 Overall flow chart of the method of the present invention.

[0022] Figure 2 Schematic diagram of the metal / dielectric multilayer anti-reflection film combination of the method of the present invention.

[0023] Figure 3 Schematic diagram of the film lamination process of the method of the present invention.

[0024] Figure 4 Schematic diagram of measuring the optical properties of dielectric films according to the method of the present invention. DETAILED DESCRIPTION

[0025] The present invention will be further explained below in conjunction with the accompanying drawings.

[0026] The overall process of the method for preparing a high-performance Micro-LED surface dielectric film according to the present invention is as follows: Figure 1As shown: In response to the optical performance requirements of the surface of the Micro-LED glass cover, this method process designs a 5-layer metal / dielectric multilayer anti-reflection film with a silicate glass structure, and uses pulsed magnetron sputtering technology with good process stability to prepare a multilayer anti-reflection film with the same film structure, and studies the influence of different process parameters on the performance of the multilayer film. In order to prepare a multilayer anti-reflection film with higher hardness, based on the single factor experiment, the hardness of the multilayer film is taken as the optimization target, and the response surface optimization method is used to design a three-factor three-level optimization experiment, and the multilayer film preparation process parameters are optimized. The corresponding process parameters when the hardness of the multilayer film is the highest are obtained and experimentally verified, and a multilayer anti-reflection film with composite hardness requirements is prepared.

[0027] according to Figure 2 The schematic diagram of the metal / dielectric multilayer anti-reflection film combination of the method of the present invention, in which ① is a dielectric material, ② is a metal material, and ③ is a substrate. This basic structural model is combined with relevant theories to establish a process for preparing thin films. First, the anti-reflection principle of the selective absorption film is based on the law of conservation of energy. The initial energy of light is equal to the sum of the energy of transmission, reflection, absorption and scattering after irradiating the object. The selective absorption film uses the high absorbance of the material itself to a certain band of light to reduce the reflectivity of the substrate surface. This type of film is usually composed of metal and dielectric. According to the microstructure of the film, it can be divided into two types: metal / dielectric composite film and metal / dielectric multilayer film. Metal / dielectric composite film is also called metal ceramic material. It is a material that embeds nano-scale metal particles into a dielectric matrix and uses the inter-band transition of metal materials to absorb light of different bands. Metal / dielectric multilayer film is based on the basic theory of optical thin film. It uses metal with a large extinction coefficient as a high refractive index material and alternately stacks it with a low refractive index dielectric material layer by layer. The thickness of each layer of material is adjusted to achieve amplitude and phase matching. The absorbance of the film layer is increased as much as possible while ensuring the transmittance, thereby achieving a low reflection effect on the substrate surface. Its structure is as follows: Figure 2 As shown. Metal / dielectric multilayer films usually use dielectric materials commonly used in optical films, and metal materials often use larger extinction coefficients. The prepared films can theoretically meet the requirement of visible light reflectivity below 2%. At the same time, the transmittance of the film layer can be adjusted according to different application requirements, and can be applied to the surface of display glass cover.

[0028] Figure 3 This is a schematic diagram of the film bonding process of the method of the present invention. In the bonding process, the bonding connection of related materials can be completed, which is divided into: dispersion is mainly achieved by spin coating, and the glue is evenly distributed on the surface of each layer. The next step is to peel off the film to isolate the area used for optical transmission. The third step is gluing, and the gluing is cured. This step can make the physical materials integrated.

[0029] Figure 4The schematic diagram of the method for measuring the optical properties of dielectric films of the present invention is to measure some optical constants of the material. The figure mainly shows the measurement method of the ellipsometry spectropolarimeter. In the figure, ① is the control system mainly used to control the sending and receiving signals and process the data; ② is the light source, which can provide light of different brightness and spectrum; ③ is the polarizer; ④ is the photoelastic modulator, which processes the incident light; ⑤ is the storage table, which is used to place the sample to be tested; ⑥ is the sample to be tested; ⑦ is the analyzer, which pre-processes the reflected light; ⑧ is the detector, which mainly collects the reflected light of the material and converts it into an electrical signal to provide data to the control system computer. The ellipsometry spectrometer incidents polarized light on the sample to be tested at a certain angle, and elliptically polarized light is formed after reflection occurs on the surface of the sample. The analyzer inside the ellipsometry spectrometer calculates the optical constants of the dielectric material according to the change of the polarization state of the incident light to the sample to be tested. The experiment uses the ellipsometry spectrometer to measure the optical constants of the film material. This figure is only a representative one, and other optical constant measurement methods are not listed one by one, such as: using a visible light spectrophotometer, an atomic force microscope and a digital microhardness tester to characterize the deposition rate, surface roughness and hardness of the multilayer film, and on the basis of a single factor experiment, taking the hardness of the multilayer film as the optimization target, the preparation process of the multilayer film is optimized. The present invention finally obtains the optical constants related to the thin film preparation.

[0030] Taking the hardness of multilayer film as the optimization target, the process parameters of preparing multilayer film were optimized by response surface method. The three factors that have the greatest influence on the hardness of multilayer film, namely, Si target power supply current intensity, Si target power supply duty cycle and argon oxygen flow ratio, were selected to design a three-factor three-level response surface experiment. The experimental model was obtained and analyzed. It was found that when the Si target power supply current was 22.076A, the Si target duty cycle was 50.857%, and the argon oxygen flow ratio was 1.313, the hardness of the multilayer film reached the optimal value. The experiment used the Si target power supply current of 22.1A, the Si target power duty cycle of 51%, and the argon oxygen flow ratio of 1.318 near the optimal process point as process parameters, and verified the optimization results. A multilayer anti-reflection film with a hardness of 830.08HV was successfully prepared. The error between the actual hardness and the expected value was less than 0.4%, indicating that the optimization method was relatively successful.

[0031] Therefore, in order to solve the problems of high reflectivity and contrast impact on the surface of untreated Micro-LED glass cover, the present invention uses optical thin film simulation analysis to optimize the structure of the Micro-LED surface film layer, and prepares multilayer films with the same structure under different process parameters, further optimizes the preparation process of the multilayer anti-reflection film, obtains the optimal process parameters and verifies them, and prepares a multilayer anti-reflection film with higher hardness. A structural film system with the best optical performance in brightness and contrast among the five-layer structures is proposed, and a suitable hardness is achieved, thereby achieving the effect of improving the luminous brightness and contrast of the Micro-LED while protecting its surface. This method provides a huge guiding role in the preparation of Micro-LED display materials and lays a good foundation for new display devices.

[0032] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a high-performance Micro-LED surface dielectric film, characterized in that: The steps include: Multilayer anti-reflection film samples with the same structure were prepared under different process parameters; Measuring the hardness of each prepared multilayer anti-reflection film sample; Taking the hardness of the multilayer anti-reflection film as the optimization target, the response surface methodology was used to optimize the process parameters for preparing the multilayer anti-reflection film and the optimal process conditions were obtained. Prepare Micro-LED surface dielectric film under optimal process conditions.

2. The method for preparing a high-performance Micro-LED surface dielectric film according to claim 1, characterized in that: The multilayer anti-reflection film comprises, from bottom to top, a substrate, a first metal layer, a first dielectric layer, a second metal layer, and a second dielectric layer.

3. The method for preparing a high-performance Micro-LED surface dielectric film according to claim 2, characterized in that: The material of the first metal layer and the second metal layer is Cr.

4. The method for preparing a high-performance Micro-LED surface dielectric film according to claim 2, characterized in that: The material of the substrate is SiO2.

5. The method for preparing a high-performance Micro-LED surface dielectric film according to claim 1, characterized in that: Multilayer anti-reflection film samples are prepared using pulsed magnetron sputtering equipment. The specific steps include: processing the incident light into monochromatic light of different wavelengths, utilizing the selective absorption of light of different bands by different substances, and converting the transmitted light into electrical signals according to the photoelectric effect to achieve the measurement of transmittance and reflectance; fitting the film thickness by the transmittance and reflectance of the film, and then calculating the deposition rate of the film according to the film preparation time, and then completing the film preparation through five steps of base pretreatment, film loading, cleaning, film preparation and film removal.

6. The method for preparing a high-performance Micro-LED surface dielectric film according to claim 2, characterized in that: The preparation method of the multilayer anti-reflection film includes: laminating each layer by spin coating, evenly distributing the glue on the surface of each layer, then peeling off the film to isolate the area used for optical transmission, the third step is gluing, and finally curing.

7. The method for preparing a high-performance Micro-LED surface dielectric film according to claim 5, characterized in that: The ellipsometer is used to make polarized light incident at a certain angle to the multilayer anti-reflection film sample to be tested. Elliptically polarized light is formed after reflection occurs on the surface of the multilayer anti-reflection film sample. The analyzer inside the ellipsometer calculates the optical constants of the dielectric material based on the change in the polarization state of the incident light of the sample to be tested. The experiment uses the ellipsometer to measure the optical constants of the film material.